Spatio-temporal distribution of grass and shrubs at the ecotone between an arid grassland and succulent shrubland : ecological interactions and the influence of soils - Shiponeni, Ndafuda Nangula (Department of Biological Sciences, 2014)
Includes bibliographical references (p. 110-122).